Influence of increasing doses and ratios of mineral fertilizers on productivity and quality of barley grain - V. D. Abashev; E. V. Svetlakova; F. A. Popov; E. N. Noskova; A. V. Denisova (Аграрная наука Евро-Северо-Востока, 2016)
Results of long-time stationary field experiment on application of mineral fertilizers on the sod-podzolic middle-clay soil generated on eluvia of Perm's clay are presented in article. There is a seventh rotation of six-field grain-fallow-grass crop rotation began in 1972-1974. The experiment pattern is a part of full factorial scheme and includes 22 variants. Dozes of nitrogen, phosphorus, and potassium are varying from 30 till 150 kg of acting matter. Barley Abava was cultivated after winter rye that follows pure fallow. Productivity of barley increased with increase in doses of fertilizers, but additions of yield is decreasing with each next doze. Productivity of barley grain is defined basically by application of nitric and phosphoric fertilizers and their interaction. Potassium fertilizers made essential impact on yield value only at their joint entering with the nitric. For barley variety Abava Ш0Р90К90 can be considered as an optimum dose which has provided productivity of 3.41 t/ha that is 2.4 times higher than without fertilizers input. At following increasing of fertilizer's doze addition of yield was insignificant in most cases. Recoupment of 1 kg of acting matter of entering fertilizers with basic production changes by a similar way. A greatest recoupment was in variants with minimum doses of nitric and phosphoric fertilizers: N60 - 15.8; К60Р60 - 13.4; Ш0Р30К30 - 11.6 kg; the lowest one -in variants: К60 - 3.8; К120 - 1.3 kg. Each next doze of fertilizers leads to lowering of barley grain's recoupment with minimum at N150P150K150 equal to 4.9 kg. Volume weight of barley grain is dependent mainly on weather conditions during growth season and harvesting time. At dry 2013 there is noted tendency to lowering the parameter with increasing of fertilizers' doze. Nitric fertilizers have raised protein content and have lowered starch content in grain. Phosphorus-and-potassium fertilizers have not affected grain quality.